Acute Alcohol Binge Deteriorates Metabolic and Respiratory Compensation Capability After Blunt Chest Trauma Followed by Hemorrhagic ShockA New Research Model - Wagner, Nils; Franz, Niklas; Dieteren, Scott; Perl, Mario; Moers, Katharina; Marzi, Ingo; Relja, Borna (Alcoholism-Clinical and Experimental Research, 2017)
BackgroundThe clinical relevance of blunt (thoracic) chest trauma (TxT) and hemorrhagic shock is indisputable due to the high prevalence of this injury type, as well as its close association with mortality and/or preventable deaths. Furthermore, there is an ongoing discussion about the influence of alcohol in trauma patients. Thus, we established a model of TxT followed by hemorrhagic shock with resuscitation (H/R) in alcohol-intoxicated rats.MethodsDepending on group allocation, 12 (subacute) or 2 (acute) hours before experimentation, the animals received a single oral dose of alcohol (ethanol [EtOH]) or saline (NaCl) followed by TxT, hemorrhagic shock (353mm Hg), and resuscitation (TxT+H/R). Arterial blood gas analyses and continuous monitoring of blood pressure were performed during the experimentation period. Survival during the experimentation procedure was determined.ResultsSubacute and acute EtOH group exhibited lower baseline mean arterial blood pressure values compared with the corresponding NaCl group, respectively. Both EtOH groups showed lower maximal bleed-out volume, which was necessary to induce hemorrhagic shock compared to NaCl groups, and the recovery during the resuscitation period was attenuated. During the experimentation in all groups, a trend to acidic pH was observed. Acute EtOH group showed lowest pH values compared to all other groups. Higher pCO(2) values were observed in both EtOH groups. All groups developed negative base excess and decreasing HCO3- values until the end of hemorrhagic shock and showed increasing base excess and HCO3- values during resuscitation. Significantly higher mortality rate was found in the acute EtOH group.ConclusionsThis study indicates that alcohol limits the metabolic and respiratory compensation capability, thereby promoting mortality.
Keywords: Alcohol; Binge; Acidosis; Respiratory; Metabolic; Blood Gas Analyses

ACUTE LUNG INJURY AFTER BLUNT CHEST TRAUMA AND HEMORRHAGIC SHOCK IS REDUCED BY ETHYL PYRUVATE VIA INHIBITION OF NF-kappa B AND HMGB1 - Perl, Mario; Wagner, Nils; Franz, Niklas; Dieteren, Scott; Schimunek, Lukas; Marzi, Ingo; Relja, Borna (Shock, 2017)

ACUTE VS. SUB-ACUTE ALCOHOL-BINGE END IN DIFFERENTIAL MORTALITY RATES, INFLAMMATORY RESPONSE AND LIVER INTEGRITY AFTER BLUNT CHEST TRAUMA FOLLOWED BY HEMORRHAGE/RESUSCITATION (H/R) IN VIVO - Relja, Borna; Wagner, Nils; Franz, Niklas; Dieteren, Scott; Moers, Katharina; Perl, Mario; Marzi, Ingo (Shock, 2016)

Aktuelle operative Therapiekonzepte traumatischer Frakturen der BWS und LWS knochengesunder Erwachsener - Spiegl, Ulrich; Pätzold, Robert; Krause, Johannes; Perl, Mario (Die Unfallchirurgie, 2024)
The surgical treatment of traumatic vertebral body fractures in patients with good bone quality is controversially discussed. The data situation is unclear and only of limited help due to mainly insufficient evidence. The surgical measures include an axially aligned reduction and an osteosynthesis which is stable under load so that immediate mobilization of the patient is possible. This requires anatomical restoration of the alignment and the biomechanical challenge of fracture healing or fusion in the correct position without relevant loss of reduction must be taken into account. The aim should be the lowest possible loss of function. In the case of existing or impending neurological deficits it is crucial to prevent deterioration of the neurological situation and to achieve the prerequisites for recovery. Posterior stabilization primarily plays the decisive role in the operative treatment. If possible, this should be a minimally invasive procedure and over short distances. For bisegmental treatment monoaxial screws and the use of index screws improve construct stability. In addition, stable cobalt rods should be used as 5mm longitudinal support. Special minimally invasive reduction instruments are helpful in restoring the sagittal and coronal relationships. The indications for an additional ventral column depend on the rigidity of the posterior stabilization, the extent of the injury of the anterior column and the intervertebral disc. Anterior fusion can often be delayed or avoided altogether, depending on the course with corresponding clinical signs.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Bone screws; Fracture osteosynthesis; Reduction; Spondylodesis; Surgical access

Alcohol Binge Reduces Systemic Leukocyte Activation and Pulmonary PMN Infiltration After Blunt Chest Trauma and Hemorrhagic Shock. - Franz, Niklas; Dieteren, Scott; Koehler, Kernt; Moers, Katharina; Sturm, Ramona; Marzi, Ingo; Perl, Mario; Relja, Borna; Wagner, Nils (Inflammation, 2019)
Blunt chest (thoracic) trauma (TxT) and hemorrhagic shock (HS)-induced local and systemic inflammation with increased neutrophil activity often result in an impaired organ function. Next to increasing the trauma risk, binge drinking causes anti-inflammatory effects due to immunomodulatory properties of alcohol (ethanol, EtOH). The impact of clinically relevant acute binge drinking scenario on local and systemic inflammatory changes, notably regarding the activity and longevity of leukocytes, has been analyzed in a combinatory trauma model of TxT + H/R. Twenty-four female Lewis rats (190-240 g) received alcohol (5 g/kg, 30%) or saline gavage. Two hours after alcohol gavage, TxT with subsequent HS (60 min) and resuscitation (TxT + H/R) were induced. Sham-operated animals underwent surgical procedures. Bronchoalveolar lavage fluid (BAL), lung tissue, and blood were harvested 2 h after resuscitation. Pulmonary infiltration with PMN, IL-6 gene expression, systemic PMN activation, neutrophil and monocyte apoptosis (caspase-3/7), and pyroptosis/inflammasome activation (caspase-1) were evaluated. Lung damage was evaluated by hematoxylin-eosin (H/E) staining and determination of the total protein content in BAL (ANOVA, p < 0.05 was significant). TxT + H/R-induced increases in IL-6, PMN infiltration and BAL-protein concentration were significantly reduced by EtOH; however, histological morphology changes after trauma remained unaltered by EtOH. TxT + H/R-induced systemic leukocyte activation (increased CD11b and CD31, reduced CD62L expression) as well as inflammasome activation in monocytes were significantly diminished by EtOH. Apoptosis was prolonged only in PMN after TxT + H/R and was further prolonged by EtOH, an effect that was observed in sham animals as a trend as well. Acute EtOH exposure inhibits the activation of circulating leukocytes after trauma compared to controls. These EtOH-driven systemic changes may be associated with reduced infiltration with PMN after trauma as well as reduced local tissue inflammation.
EVALuna2:415870

Alcohol‑induced attenuation of post‑traumatic inflammation is not necessarily liver‑protective following trauma/hemorrhage. - Wagner, Nils; Dieteren, Scott; Franz, Niklas; Koehler, Kernt; Perl, Mario; Marzi, Ingo; Relja, Borna (International Journal of Molecular Medicine, 2019)
Due to their high prevalence, blunt chest trauma (TxT) and hemorrhagic shock have a significant influence on the outcomes of trauma patients, causing severe modulations of the immune system and high mortality rates. Alcohol consumption in trauma patients has a high clinical impact. Studies investigating the timing of alcohol intoxication prior to trauma are limited, although there are two typical scenarios regarding alcohol consumption: Acute ('drink and drive scenario') and sub‑acute ('evening binge drinking'). Therefore, the present study investigated the influence of either an acute or sub‑acute alcohol‑drinking scenario in an in vivo model of TxT and hemorrhagic shock, focusing on liver inflammation and outcomes. At 12 h (sub‑acute) or 2 h (acute) before the experiment, female Lewis rats received a single oral dose of alcohol (ethanol, EtOH) or saline (NaCl, ctrl), followed by TxT, hemorrhagic shock (35±3 mm Hg) and resuscitation (H/R). The animals were either sacrificed 2 h later or their survival was determined for 72 h. The results revealed that EtOH induced significant fatty changes in the liver. TxT + H/R‑induced increases in the gene expression of interleukin (IL)‑6 and intercellular adhesion molecule‑1 and the protein expression of tumor necrosis factor (TNF)‑α and IL‑1β were significantly reduced in both EtOH groups compared with those in the corresponding TxT + H/R ctrl groups. The local presence of IL‑10‑expressing cells in the liver was significantly increased following TxT + H/R in all groups, although the sub‑acute EtOH TxT + H/R group had a significantly higher proportion of IL‑10‑positive cells compared with all other groups. Stimulating peripheral whole blood with lipopolysaccharide led to significantly lower levels of TNF‑α release in the sub‑acute EtOH group compared with the levels in all other groups. Significant TxT + H/R‑induced increases in liver transaminases and liver damage were most prominent in the sub‑acute EtOH group. The TxT + H/R EtOH group exhibited the lowest levels of glucose. There were no significant differences in mortality rate among the TxT + H/R groups. The data obtained indicates that the severity of liver damage following TxT + H/R may depend on the timing of alcohol consumption and severity of trauma, but also on the balance between pro‑ and anti‑inflammatory responses.
EVALuna2:415869

Biomechanical comparison of acetabular fracture fixation with stand-alone THA or in combination with plating - Wenzel, Lisa; Sandriesser, Sabrina; Glowalla, Claudio; Gueorguiev, Boyko; Perl, Mario; Stuby, Fabian M.; Augat, Peter; Hungerer, Sven (European Journal of Trauma and Emergency Surgery, 2022)
Purpose A common surgical treatment in anterior column acetabular fractures with preexisting osteoarthritis is THA, which is commonly combined with plate osteosynthesis. Implantation of a solitary revision cup cranially fixed to the os ilium is less common. The purpose of this study was to compare the stabilization of anterior column acetabular fractures fixed with a cranial socket revision cup with flange and iliac peg or with a suprapectineal plate osteosynthesis combined with an additional revision cup. Methods In 20 human hemipelves, an anterior column fracture was stabilized by either a cranial socket revision cup with integrated flange (CF = Cup with Flange) or by a suprapectineal plate combined with a revision cup (CP = Cup and Plate). Each specimen was loaded under a stepwise increasing dynamic load protocol. Initial construct stiffness, interfragmentary movements along the fracture line, as well as femoral head movement in relation to the acetabulum were analyzed. Results Both groups showed comparable initial construct stiffness (CP: 3180 +/- 1162 N/mm and CF: 3754 +/- 668 N/mm; p = 0.158). At an applied load of 1400 N, interfragmentary movements at the acetabular (p = 0.139) and the supraacetabular region (p = 0.051) revealed comparable displacement for both groups and remained below 1 mm. Femoral head movement in relation to the acetabulum also remained below 1 mm for both test groups (p = 0.260). Conclusion From a biomechanical point of view, both surgical approaches showed comparable fracture reduction in terms of initial construct stiffness and interfragmentary movement. The potential benefit of the less-invasive cranial socket revision cup has to be further investigated in clinical studies.
CRIS-Team WoS Importer:2022-01-21

Chances and Risks of a new Residency Program for Orthopedics and Trauma Surgery - Merschin, David; Muenzberg, Matthias; Perl, Mario (Zeitschrift für Orthopädie und Unfallchirurgie, 2013)
Background: The residency program for a specialist in orthopedics and trauma surgery is facing fundamental changes based on an initiative originating from the working group medical training" of the German Medical Association (GMA). A survey indicated that 50% of all trainees are dissatisfied with their current situation. It appears important to integrate the ideas and wishes of current orthopedic residents in a novel training concept. To assess this a survey was performed by the Young Forum of the German Society for Orthopedics und Trauma Surgery.Material and Methods: The internet-based short survey was conducted in January 2013 among members of the professional societies (DGU, DGOU and DGOOC). 408 physicians participated.Results: The majority of the participating physicians is interested in a career in orthopedics and trauma surgery with primarily operative contents. Accordingly the majority (62%, n=253) voted against a reduction of numbers of surgical interventions with 86% (n=351) confirming the necessity that these operations must be carried out by the trainee himself.Conclusion: The upcoming changes in residency program for orthopedics and trauma surgery offer the oportunity for a well structured and practical oriented residency program. It could be a furhter step in increasing satisfaction in this profession.
Keywords: residency program; orthopedics and trauma surgery; Youth Forum of the DGOU

CIRCULATING C5A RECEPTOR TO MONITOR SEPSIS? - Denk, S.; Rittirsch, D.; Barth, H.; Perl, Mario; Ward, P.; Huber-Lang, M. (Shock, 2014)

Combined Odontoid (C2) and Atlas (C1) Fractures in Geriatric Patients: A Systematic Review and Treatment Recommendation - Spiegl, Ulrich J.A.; Keil, Holger; Krause, Julia; Osterhoff, Georg; Scheyerer, Max J.; Schnake, Klaus John; Perl, Mario (Global Spine Journal, 2023)
Study Design: Systematic review. Objective: The aim of this study was to conduct a systematic overview of the pathogenesis and the treatment options of combined odontoid and atlas fractures in geriatric patients. Methods: This review is based on articles retrieved by a systematic search in the PubMed and Web of Science databases for articles published until February 2021 dealing with combination fractures of C1 and C2 in geriatric patients. Results: Altogether, 438 articles were retrieved from the literature search. A total of 430 articles were excluded. The remaining eight original articles were included in this systematic review depicting the topics pathogenesis, non-operative treatment, posterior approach, and anterior approach. The overall level of evidence of the studies is low. Conclusion: Combined odontoid and atlas fractures in the geriatric population are commonly caused by simple falls and seem to be associated with atlanto-odontoid osteoarthritis. Non-operative treatment with a cervical orthosis is a feasible treatment option in the majority of patients with stable C2 fractures. In case of surgery posterior C1 and C 2 stabilization and anterior triple or quadruple screw fixation are possible techniques. Some patients may also deserve an occipito-cervical fusion. A possible treatment algorithm is proposed.
CRIS-Team Scopus Importer:2023-05-05

Comparing the outcome after double level osteotomies in severe valgus and varus knees - Sendner, Theresa; Schubert, Ilona; Spahic, Mirsad; Reuter, Benoit; Perl, Mario; Dickschas, Jörg (Archives of Orthopaedic and Trauma Surgery, 2025)
Introduction: Osteotomies have played an important role in joint preservation surgery of the knee joint for many years. A double level osteotomy is performed for severe varus or valgus deformities. There are numerous publications on double level osteotomies for severe varus deformities, whereas there are no publications on valgus deformities. The hypothesis of this study was to compare the clinical outcome after varus DLO with that after valgus DLO. Material and methods: In this retrospective study, 40 DLOs were followed up in 34 patients. In group one (13 cases, age 45.6 (16–61) years) a varization DLO was performed, in group two (24 cases, age 48.3 (20–61) years) a valgization DLO was performed. The pre- and postoperative clinical scores were recorded: Tegner Activity score, Japanese knee society Score and Lysholm Score. The leg axis and knee joint angles were recorded and compared pre- and postoperatively. Results: The follow-up period was 24 (6–81) months. The follow-up rate was 73% (27/37). The preoperative leg axis in group one showed an average valgus of 15.9° (9–40°). Group two had an average varus of 12° (8–21°). Postoperatively, the leg axis was 3.4° varus in group one and 0.5° valgus in group two. The mLDFA changed in group one from 83.2° to 90.9°, the MPTA from 95.5° to 87.0°. In group two, the mLDFA changed from 91.9° to 85.9° and the MPTA from 83.3° to 88.3° on average. The JLCA changed in group one from − 3.2 (− 5°–0°) to − 0.5° (− 3–2°) postoperative and in group two from 3.3° (1–8°) to 3.0° (0–6°) postoperative. Tegner score, Lysholm score and Japanese knee Society score all improved significantly in both groups. Patients with a valgus axis have worse clinical scores before surgery than the varus group, but the varus group shows a higher potential for improvement postoperatively. Every patient stated that they would have the operation performed again. Complications were rare, two overcorrections required corrective surgery. Two hinge fractures were treated intraoperatively with additional contralateral plate osteosynthesis. Conclusions: Patients show very good clinical results after DLO. The improvements in the valgus knees are greater, but starting from a lower preoperative level, probably due to improvements in both the lateral compartment and the patellofemoral compartment. An important finding was that JLCA is normalizing in valgization DLO but not in varization DLO. This needs to be considered in planning a DLO.
CRIS-Team Scopus Importer:2025-05-23
Keywords: DLO; Double level osteotomy; Genu valgum; Genu varum; Valgization; Varization

Comparison of Effective Dose From Intraoperative 3D Imaging Using Mobile and Fixed C-Arms Versus Computed Tomography When Evaluating the Lumbar Spine - Stadthalter, Holger; Grafenberg, A.; Liebegut, U.; Stepina, E.; Brehm, M.; Perl, Mario (Global Spine Journal, 2025)
Study design: Experimental Study. Objectives: Intraoperative three-dimensional (3D) imaging has been shown to increase patient safety by assuring proper implant placement and often makes postoperative CT imaging obsolete. Nonetheless, there is no data about effective radiation doses in comparison to CT imaging. Methods: Effective doses of 3D and CT scans were measured with an anthropomorphic phantom (CIRS Inc, ATOM® Dosimetry Phantoms, Norfolk, VA, USA). Clinical presets of the C-arms were used and measured separately (mobile: Cios Spin; fixed: ARTIS pheno; both Siemens Healthcare GmbH, Erlangen, Germany). For CT imaging, a protocol for high-contrast imaging was used (SOMATOM X.cite, Siemens Healthcare GmbH, Erlangen, Germany). Results: Depending on presets, effective doses with the mobile C-arm ranged from.51 ±.02 mSv (dose-sparing preset) to 3.14 ±.01 mSv (high-quality preset, P <.001). With the fixed C-arm, the effective dose ranged from.52 ±.0 mSv (dose-sparing preset) to 1.6 ±.02 mSv (standard-quality preset, P <.001). With CT imaging, the effective dose was 2.0 mSv. Conclusions: When evaluating the lumbar spine, the effective dose from intraoperative 3D imaging using mobile and fixed C-arms is comparable to that from CT scans. Proper choice of intraoperative protocol is essential, as there can be up to a 6-fold variation in dose between protocols. Intraoperative 3D imaging with (mobile or fixed) C-arms has been proven to avoid revision surgery. In this study, effective doses were shown to be comparable to those of CT scans. To avoid unnecessary exposure, indications need to be clear, and the choice of acquiring settings must respect the ALARA principle (“as low as reasonably achievable”).
CRIS-Team Scopus Importer:2025-05-16
Keywords: computed tomography dose; dose comparison; imaging spine; intraoperative 3D imaging

Comparison of In Vivo Stiffness of Tendons Commonly Used for Anterior Cruciate Ligament Reconstruction – A Shear Wave Elastography Study - Pasurka, Mario; Falck, Theo; Kubach, Joshua; Simon, Michael; Söllner, Stefan; Strobel, Deike; Perl, Mario; Betsch, Marcel (Academic Radiology, 2024)
Rationale and Objectives: There are currently no studies investigating the in vivo stiffness of the most commonly used autografts for anterior cruciate ligament reconstruction (ACLR) using Shear wave elastography (SWE). We hypothesize that there are differences regarding the elastic properties between the three tendons commonly used for ACLR and that they are influenced by patient-related factors. Materials and Methods: 80 healthy subjects (25 females, 55 males, age: 25.33 ± 4.76 years, BMI: 23.76 ± 3.14 kg/m2, 40 semiprofessional athletes, athlete group [AG], age: 25.51 [19–29]; 40 healthy controls, control group [CG], age: 25.50 [20–29]) were recruited as participants. In addition to patient reported outcome scores, every participant underwent a standardized multimodal ultrasound protocol consisting of B-mode-ultrasound (B-US), Color Doppler-ultrasound (CD-US) and a SWE examination of the bilateral quadriceps tendon (QT), patellar tendon (PT) and semitendinosus tendon (ST). Results: The highest shear wave velocity (SWV) were observed in ST (4.88 (4.35–5.52) m/s, ST vs QT, p = 0.005; ST vs PT, p < 0.001) followed by QT (4.61 (4.13–5.26) m/s, QT vs PT, p < 0.001) and PT (3.73 (3.30–4.68) m/s). Median QT, PT and ST stiffness was significantly higher in AG compared to CG. Male subjects tend to have stiffer QT and PT than female subjects. Positive correlation with SWV was obtained for age and activity level. Conclusion: There are significant differences regarding in vivo tendon stiffness between the most frequently used autograft tendon options for ACLR. The quantitative information obtained by SWE could be of particular interest for graft choice for ACLR.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Musculoskeletal ultrasound; Shear wave elastography; Tendon stiffness

Complement Factor C5a Inhibits Apoptosis of Neutrophils-A Mechanism in Polytrauma? - Ehrnthaller, Christian; Braumueller, Sonja; Kellermann, Stephanie; Gebhard, Florian; Perl, Mario; Huber-Lang, Markus (Journal of Clinical Medicine, 2021)
Life-threatening polytrauma results in early activation of the complement and apoptotic system, as well as leukocytes, ultimately leading to the clearance of damaged cells. However, little is known about interactions between the complement and apoptotic systems in PMN (polymorphonuclear neutrophils) after multiple injuries. PMN from polytrauma patients and healthy volunteers were obtained and assessed for apoptotic events along the post-traumatic time course. In vitro studies simulated complement activation by the exposure of PMN to C3a or C5a and addressed both the intrinsic and extrinsic apoptotic pathway. Specific blockade of the C5a-receptor 1 (C5aR1) on PMN was evaluated for efficacy to reverse complement-driven alterations. PMN from polytrauma patients exhibited significantly reduced apoptotic rates up to 10 days post trauma compared to healthy controls. Polytrauma-induced resistance was associated with significantly reduced Fas-ligand (FasL) and Fas-receptor (FasR) on PMN and in contrast, significantly enhanced FasL and FasR in serum. Simulation of systemic complement activation revealed for C5a, but not for C3a, a dose-dependent abrogation of PMN apoptosis in both intrinsic and extrinsic pathways. Furthermore, specific blockade of the C5aR1 reversed C5a-induced PMN resistance to apoptosis. The data suggest an important regulatory and putative mechanistic and therapeutic role of the C5a/C5aR1 interaction on PMN apoptosis after polytrauma.
CRIS-Team WoS Importer:2021-08-06

CPR related injuries of the chest wall: direct and indirect fractures - Schenderlein, Anne; Groh, Johannes; Kern, Florian; Perl, Mario; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2025)
BACKGROUND: Rib and sternum fractures are common injuries associated with cardiopulmonary resuscitation (CPR). The fracture mechanism is either direct by application of force on sternum and anterior ribs or indirect by bending through compression of the thorax. The aim of this study was to determine morphologies of rib fractures after CPR and to reevaluate prior findings on fracture localisation, type and degree of dislocation. METHODS: The present study was based on all inpatients treated for chest wall fractures after non traumatic cardiac arrest at a Level 1 Trauma Centre from 2010 to 2016 who had received CT scans. Each fracture was analyzed for location, degree of dislocation and fracture type classified according to AO/OTA and CWIS. We also analysed Fracture Line orientation. RESULTS: We enrolled 40 patients with a total of 423 rib fractures. We found most fractures anterolaterally between the 3rd to 6th rib symmetrically on both sides of the thorax. We found sternum fractures in 30% of the patients, 50% being located at the at the corpus sterni between rib 3 and 4. All patients with sternum fractures suffered from rib fractures and most had fractures of the cartilage or osteochondral junction. All cartilage fractures were straight, undisplaced type A fractures. Most indirect fractures occurred anterolaterally between 50 and 60° in the axial plane. More than 90% of those fractures were classified as type A, 70% showed a straight fracture line and 60% were undisplaced. There was no difference in degree of dislocation between straight and oblique fracture lines. We found 143 incomplete fractures. CONCLUSION: We confirmed prior findings regarding fracture patterns in CPR related injuries. We observed approximately 2-3 times as many straight-lined fractures as oblique ones following indirect trauma. One third of all fractures are incomplete, these highlights the special characteristics like high elasticity of ribs.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Chest wall injury; CPR; Flail chest; Fracture morphology; Indirect fractures; Rib fractures

Daily Routine in Orthopedics and Traumatology - Results of a Nationwide Survey of Residents - Merschin, David; Muenzberg, M.; Stange, R.; Schuettrumpf, J. P.; Mutschler, M.; Perl, Mario (Zeitschrift für Orthopädie und Unfallchirurgie, 2014)
Background: The subject orthopedics and traumatology suffers by a loss of attractiveness which results in a lack of young blood. The aim of this study of the Youth Forum of the German Society of Orthopedics and Traumatology (DGOU) is to register the working conditions of residents in orthopedics.Material and Methods: In the months September and October 2013 we performed a survey on members of the following German societies: German Society of Orthopedics and Traumatology (DGOU), German Society of Traumatology (DGU) and the German Society of Orthopedics and Orthopedic Surgery (DGOOC), (age < 40). Our questionnaire includes 15 questions.Results: We achieved 28,9% (n = 331) answered questionnaires. The mean working time per week is 55 hours. 73% of all participants do more than 5 emergency services per month. 52% are more than 3 times on duty for 24 hours. Only 13% of all residents have well ordered working hours. Normally working time is divided into three parts: one third for bureaucracy, one for operation theatre and the last for other activities (e. g. ward round). 35,6% do only one surgery per week, 12% do not perform any surgeries. An annual report is performed only in 45%. A structured concept of training only exists in 16% of all hospitals. In addition to clinical work 45% are involved in scientific projects, mostly in their spare-time. Finally 58% of all surgeons would still recommend orthopedics and traumatology.Conclusion: In order to maintain orthopedics and traumatology as an attractive it is necessary to implement flexible working time models and to reorganize and improve training-concepts.
Keywords: residency; working condition; resident shortage; youth forum

Der Pararectus-Zugang: operatives Vorgehen in der Acetabulumchirurgie - von Rüden, Christian; Brand, Andreas; Perl, Mario (Operative Orthopadie und Traumatologie, 2023)
Objective: The pararectus approach was rediscovered several years ago for pelvic surgery and described as an alternative approach especially for the treatment of acetabular fractures of the anterior column involving the quadrilateral plate. Indications: For optimal visualization of acetabular fractures involving the quadrilateral plate, fractures of the anterior wall and anterior column, anterior column/posterior hemitransverse fractures, and fractures with central impression of dome fragments, the pararectus approach has proven to be a useful access. Contraindications: The pararectus approach is not used for posterior column fractures, posterior wall fractures, combined posterior wall and posterior column fractures, transverse fractures with displaced posterior column or in combination with posterior wall fractures, and T‑fractures with displaced posterior column or in combination with posterior wall fractures. Surgical technique: The entire pelvic ring, including the quadrilateral plate, can be accessed via the pararectus approach. The choice of the correct surgical window depends on the fracture location and the requirements of fracture reduction. Postoperative management: In general, partial weight-bearing should be maintained for 6 weeks, although earlier weight-bearing release may be possible if necessary, depending on fracture pattern and osteosynthesis. Particularly in geriatric patients, partial weight-bearing is often not possible, so that early and often relatively uncontrolled full weight-bearing has to be accepted. Results: In a comparative gait analysis between patients following surgical stabilization of an isolated unilateral acetabular fracture through the pararectus approach and healthy subjects, sufficient stability and motion function of the pelvis and hip during walking was already evident in the early postoperative phase.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Acetabular fracture; Anterior column/anterior wall fracture; Gait analysis; Internal fracture fixation; Quadrilateral surface

Development of a deep learning algorithm for radiographic detection of syndesmotic instability in ankle fractures with intraoperative validation - Kubach, Joshua; Pogarell, Tobias; Uder, Michael; Perl, Mario; Betsch, Marcel; Pasurka, Mario; Söllner, Stefan; Heiß, Rafael (Scientific Reports, 2025)
Identifying syndesmotic instability in ankle fractures using conventional radiographs is still a major challenge. In this study we trained a convolutional neural network (CNN) to classify the fracture utilizing the AO-classification (AO-44 A/B/C) and to simultaneously detect syndesmosis instability in the conventional radiograph by leveraging the intraoperative stress testing as the gold standard. In this retrospective exploratory study we identified 700 patients with rotational ankle fractures at a university hospital from 2019 to 2024, from whom 1588 digital radiographs were extracted to train, validate, and test a CNN. Radiographs were classified based on the therapy-decisive gold standard of the intraoperative hook-test and the preoperatively determined AO-classification from the surgical report. To perform internal validation and quality control, the algorithm results were visualized using Guided Score Class activation maps (GSCAM).The AO44-classification sensitivity over all subclasses was 91%. Furthermore, the syndesmosis instability could be identified with a sensitivity of 0.84 (95% confidence interval (CI) 0.78, 0.92) and specificity 0.8 (95% CI 0.67, 0.9). Consistent visualization results were obtained from the GSCAMs. The integration of an explainable deep-learning algorithm, trained on an intraoperative gold standard showed a 0.84 sensitivity for syndesmotic stability testing. Thus, providing clinically interpretable outputs, suggesting potential for enhanced preoperative decision-making in complex ankle trauma.
CRIS-Team Scopus Importer:2025-08-29

Die Double-Level-Derotationsosteotomie am Kniegelenk - Ferner, Felix; Lutter, Christoph; Perl, Mario; Harrer, Jörg (Zeitschrift für Orthopädie und Unfallchirurgie, 2023)
CRIS-Team Scopus Importer:2024-12-16

Die operative Versorgung einer bimalleolären OSG-Fraktur – Tipps und Tricks - Mayr, Jakob; Schramm, Simon; Renner, Nina; Perl, Mario; Palm, Hans Georg (Zeitschrift für Orthopädie und Unfallchirurgie, 2024)
CRIS-Team Scopus Importer:2024-05-24

Die präventive Flexionsosteotomie am Tibiakopf - Reuter, Benoit; Perl, Mario; Dickschas, Jörg (Sportverletzung-Sportschaden, 2024)
Die folgende Falldarstellung berichtet über eine präventive Tibiakopf-Flexionsosteotomie bei einem jugendlichen Patienten, bei welchem ein erniedrigter posteriorer Slope des Tibiakopfes vorlag. Der Patient zeigte sich zu diesem Zeitpunkt symptomfrei und ohne Instabilität. MR-tomografisch zeigte sich jedoch eine ausgeprägte Veränderung des hinteren Kreuzbandes, was als Indikation zur Osteotomie interpretiert wurde. Die OP-Technik und das postoperative Resultat werden dargestellt. Das postoperative MRT zeigt eine Reorganisation des hinteren Kreuzbandes in eine physiologische Konfiguration.
CRIS-Team Scopus Importer:2025-02-04
Keywords: posterior cruciate ligament; tibial plateau flexion osteotomy

DIVERGENT EFFECTS OF NECROTIC AND APOPTOTIC LUNG EPITHELIAL CELLS IN THE PATHOGENESIS OF CHEST TRAUMA INDUCED SEPTIC ACUTE LUNG INJURY (ALI) - Hohmann, C.; Kellermann, P.; Schultze, A.; Klohs, B.; Huber-Lang, M.; Perl, Mario (Shock, 2014)

DIVERGENT EFFECTS OF NEUTROPHILS ON FAS-INDUCED PULMONARY INFLAMMATION, APOPTOSIS, AND LUNG DAMAGE - Bruns, Bastian; Hoenle, Theresia; Kellermann, Philipp; Ayala, Alfred; Perl, Mario (Shock, 2017)
Pulmonary Fas activation is essential in the pathogenesis of the acute respiratory distress syndrome. It remains unclear whether Fas-induced lung injury is dependent on neutrophils or mainly triggered by epithelial cell apoptosis. The contribution of lung epithelial cells (LEC) and alveolar macrophages (AM) remains elusive. Mice were neutrophil reduced prior to intratracheal instillation of Fas-activating (Jo2) or isotype antibody for 6 or 18 h. LEC and AM were incubated with Jo2 and in the presence of nuclear factor kappa B, p-38 mitogen activated protein kinase (p38MAPK), or extracellular signal regulating kinase 1/2 (ERK1/2) inhibitors. Cytokines were assessed by cytometric bead array or ELISA. Apoptosis was quantified via active caspase-3 Western blotting and Terminal Deoxynucleotide Transferase dUTP Nick End Labeling (TUNEL). Lung injury was assessed by bronchoalveolar lavage fluid (BALF) protein concentration and lung histology. KC, IL-6, and MCP-1 were markedly increased in lung, plasma, and BALF 18 h after Jo2 in the presence of neutrophils; in neutrophil-reduced mice lungs, MCP-1, but not KC or IL-6, was even further enhanced. Six hours after Jo2, BALF protein was markedly increased only in the presence of neutrophils. Apoptosis remained unaffected by neutrophil reduction. AM released MCP-1 and underwent apoptosis at lower concentrations of Jo2 than LEC. Inhibition of p38MAPK significantly increased, while inhibition of ERK1/2 reduced AM and LEC apoptosis. In conclusion, neutrophils are a necessary component of Fas-induced lung damage, while not affecting lung apoptosis directly per se. LEC display higher resistance to Fas-triggered inflammation and apoptosis than AM.
Keywords: ALI; alveolar macrophages; ARDS; cytokines; lung epithelial cells; neutrophil depletion

Double-level torsional osteotomy a treatment for the 'inwardly pointing knee' syndrome. - Liße, Jens; Perl, Mario; Dickschas, Jörg (Archives of Orthopaedic and Trauma Surgery, 2023)
INTRODUCTION: A 'inwardly pointing knee' syndrome is a combined torsional deformity with increased femoral internal and tibial external torsion. After clinical and radiological verification of the torsional deformity and unsuccessful conservative therapy approach, a combined (double level) torsional osteotomy of femur and tibia might be the appropriate treatment. Here, we present the diagnostic algorithms, treatment, and outcome of combined torsional osteotomies of femur and tibia. The aim of the study is to show that patients treated with the procedure achieve patellofemoral stability and pain relief or reduction. MATERIAL AND METHODS: Twenty torsional osteotomies performed on 18 patients were included. Nine patients had experienced patellar dislocation in 11 joints before. All patients were suffering from anterior knee pain. All patients underwent a clinical and radiographical evaluation, including a torsion angle CT scan. Pre- and post-operatively multiple commonly approved scores (Lysholm Score, Tegner Activity score, Kujala Score, VAS and Japanese Knee Society score) were acquired. RESULTS: In 18 patients we performed 20 double-level torsional osteotomies. 9 patients suffered from patellar dislocations in 11 knee joints prior to surgery. All patients were suffering from anterior knee pain. Of these 7 patients achieved a stable joint after surgery without further patellar dislocations. All achieved more knee stability and experienced less patellar luxation then before surgery. The mean duration of follow-up was 59 months (range 9-173 months). The mean VAS was significantly reduced by 3.75 points (SD 2.09, p value 0.0002) from 5.50 points (SD 2.73, range 0-9) before surgery to 1.75 points (SD 1.67, range 0-5) after surgery. The Lysholm score increased significantly by mean of 27.6 (SD 17.55, p value 0.0001) from mean 62.45 (SD 22.71, range 22-100) before surgery to mean 90.05 (SD 10.18, range 66-100) after surgery. The Kujala Score did improve significantly in average by 25.20 points (SD 13.61, p value 0.00012) from mean 62.9 (SD 16.24, range 35-95) to mean 93.2 (SD 9.20, range 66-100). The Tegner activity score did increase significantly by 1.2 points (SD 1.47, p value 0.004) in average from mean 2.65 (SD 1.11, range 1-5) to mean 3.85 (SD 1.42, range 1-6). The Japanese knee score did increase significantly by 19.15 in average (SD 11.95, p value 0.0001) from mean 74.05 (SD 14.63, range 33-95) to mean 93.05 (SD 10.18, range 68-100). CONCLUSION: This is the first publication reporting about simultaneous double-level torsional osteotomies in a comparatively high number of patients. In addition, this is the first publication assessing the patient collective afterwards with objectifying clinical outcome scores. The results show that double-level torsional osteotomy is an effective treatment for patients with patellar dislocation or subluxation associated to torsional deformities of femur and tibia. Furthermore, we introduce a diagnostic algorithm for 'inwardly pointing knee' syndrome. LEVEL OF EVIDENCE: Level IV.
EVALuna2:591173

Do we have to redefine type B-fractures of the rib cartilage? - Groh, Johannes; Kern, Florian; Perl, Mario; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2024)
Objectives: Aim of this work was the evaluation and validation of the AO/OTA classification of the anterior chest wall, here especially for the rib cartilage. Methods: Study design was a retrospective analysis of patients who were hospitalized with fractures of the thoracic wall in the years 2010–2016. This resulted in a collective of n = 124 patients. All fractures of the anterior chest wall were classified according to their location, dislocation and fracture type according to the AO classification. An analysis of possible subtypes was carried out. Results: 29.0% (36) of the patients had fractures of the rib cartilage. 23 of the 36 (64%) patients had multiple fractures, the total number of single fractures amounted to 94. 53.2% (50) of these fractures were in the right hemithorax, 46.8% (44) in the left hemithorax. 95.7% (90) of the fractures were A-fractures, 4.3% (4) were C-fractures. There were no B fractures. The C fractures also consisted exclusively of A fractures (AA fractures). 59.6% (56) of the fractures showed a dislocation. 30.9% (29) were avulsion fractures of either the osteochondral (22.3% (21)) or the sternocostal junction (8.5% (8)). Discussion and conclusion: The costal cartilage obviously does not show typical B fractures as we know them from shaft fractures of long bones. We have compiled a structured analysis in the attached manuscript and validated the classification proposal. In conclusion, we propose an adaptation of the classification proposal based on our data with redefining type B fractures as fractures of the osteochondral joints.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Anterior rib; AO/OTA classification; Costal cartilage; Costochondral; Rib cartilage; Rib fracture; Sternocostal

Early biomechanical outcome in patients with acetabular fractures treated using the pararectus approach: a gait and stair climb analysis study - Brand, Andreas; von Rüden, Christian; Probst, Carina; Wenzel, Lisa; Augat, Peter; Perl, Mario (European Journal of Trauma and Emergency Surgery, 2021)
Purpose: Patients with surgically treated acetabular fractures using extensive dissection of hip muscles demonstrate an incomplete biomechanical recovery and limited joint mobility during movement. The purpose of this study was to evaluate the early biomechanical outcome in a series of patients with acetabular fractures treated using the less invasive anatomical pararectus approach. Methods: Eight patients (48 ± 14 years, BMI 25.8 ± 3 kg/m2) were investigated 3.8 ± 1.3 months after surgery and compared to matched controls (49 ± 13 years, BMI 26 ± 2.8 kg/m2). Trunk and lower extremity kinematics and kinetics during gait and stair climb were calculated. SF-12 and the Merle d’Aubigné score were used for functional evaluation. Statistical analysis was conducted using Mann–Whitney test and Student’s t test. Effect sizes were calculated using Cohen’s d. Results: No group differences for lower extremity kinematics during walking and stair climbing were found. During walking, patients showed significant reductions (p < 0.05) of the vertical ground reaction force (8%) and knee and hip extension moments (29 and 27%). Ipsilateral trunk lean was significantly increased by 3.1° during stair descend while reductions of vertical ground reaction force were found for stair ascend (7%) and descend (20%). Hip extension moment was significantly reduced during stair descend by 37%. Patients revealed acceptable SF-12 physical and mental component outcomes and a good rating for the Merle d’Aubigné score (15.9 ± 1.7). Conclusion: Patients showed some biomechanical restrictions that can be related to residual deficits in weight bearing capacity and strength of the hip muscles. In contrast, an immediate recovery of mobility was achieved by preserving lower extremity and pelvic movement. Therefore, the pararectus approach can serve as a viable strategy in the surgical treatment of acetabular fractures. Clinical trial: Trial registration number DRKS00011308, 11/14/2016, prospectively registered.
CRIS-Team Scopus Importer:2021-04-23
Keywords: Acetabular fracture; Biomechanics; Functional outcome; Gait analysis; Pararectus approach

EFFECTS OF COMBINED SILENCING OF CASPASE-3, FADD AND FAS ON THE PATHOGENESIS OF CHEST TRAUMA INDUCED SEPTIC ACUTE LUNG INJURY (ALI) - Hohmann, C.; Kellermann, P.; Weber, S.; Schaupp, F.; Huber-Lang, M.; Perl, Mario (Shock, 2014)

Efficacy of a new treatment algorithm for capsulitis of the fingers in rock climbers - Schöffl, Volker; Lutter, Christoph; Lang, Hans Christoph; Perl, Mario; Moser, Othmar; Simon, Michael (Frontiers in Sports and Active Living, 2025)
Background: Although finger joint capsulitis has been described among the most frequent injuries in climbers, no clinical studies on treatment strategies and outcomes are available. Study design: Prospective case series study. Methods: Between 2015 and 2018 we prospectively treated 50 patients (38 male, 12 female) with a total number of 69 independent finger joint capsulitis according to a clinic specific treatment regimen and evaluated the outcome retrospectively. Therapy consisted of either conservative management, steroid injections, radiosynoviorthesis or a combination depending on the treatment regimen, prior therapy and timeline of symptoms. Outcomes were assessed using visual analogue scale (VAS), Buck-Gramcko score and a climbing specific outcome score with secondary patient recall. Results: The proximal interphalangeal joint of the middle finger was the most commonly affected joint, and there was no correlation with osteoarthritis. All climbers returned to sport within 12 months. The majority were able to maintain their level of performance after injury and the difference in climbing level before and after injury was not statistically significant (p = 0.22). The total time spent climbing was significantly less after the injury than before the injury (p < 0.001). The Buck-Gramcko score showed excellent results. The overall functional outcome was good to very good with a mean score of 1.6 ± 0.7, as was the climbing specific score of 1.7 ± 0.9. Pain was significantly less after treatment than before (p < 0.001). Conclusion: Good to very good functional and sport-specific outcomes were seen with the stage-specific treatment regimen presented, allowing all patients studied to resume climbing. A better understanding of the underlying pathogenesis is essential in order to better assess long-term progress.
CRIS-Team Scopus Importer:2025-02-14
Keywords: capsulitis; finger injuries; finger joint synovitis; rock climbing; sport climbing

Ethanol Decreases Inflammatory Response in Human Lung Epithelial Cells by Inhibiting the Canonical NF-kappa B-Pathway - Moers, Katharina; Hoerauf, Jason-Alexander; Kany, Shinwan; Wagner, Nils; Sturm, Ramona; Woschek, Mathias; Marzi, Ingo; Relja, Borna; Perl, Mario (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Alcohol (ethanol, EtOH) as significant contributor to traumatic injury is linked to suppressed inflammatory response, thereby influencing clinical outcomes. Alcohol-induced immune-suppression during acute inflammation (trauma) was linked to nuclear factor-kappaB (NF-kappa B). Here, we analyzed alcohol's effects and mechanisms underlying its influence on NF-kappa B-signaling during acute inflammation in human lung epithelial cells. Methods: A549-cells were stimulated with interleukin (IL)-1 beta, or sera from trauma patients (TP) or healthy volunteers, with positive/negative blood alcohol concentrations (BAC), and subsequently exposed to EtOH (170 Mm, 1h). IL-6-release and neutrophil adhesion to A549 were analyzed. Specific siRNA-NIK mediated downregulation of non-canonical, and IKK-NBD-inhibition of canonical NF-kappa B signaling were performed. Nuclear levels of activated p50 and p52 NF-kappa B-subunits were detected using TransAm ELISA. Results: Both stimuli significantly induced IL-6-release (39.79 +/- 4.70 vs. 0.58 +/- 0.8 pg/ml) and neutrophil adhesion (132.30 +/- 8.80 vs. 100% control, p < 0.05) to A549-cells. EtOH significantly decreased IL-6-release (22.90 +/- 5.40, p < 0.05) and neutrophil adherence vs. controls (105.40 +/- 14.5%, p < 0.05). IL-1 beta-induced significant activation of canonical/p50 and non-canonical/p52 pathways. EtOH significantly reduced p50 (34.90 +/- 23.70 vs. 197.70 +/- 36.43, p < 0.05) not p52 activation. Inhibition of canonical pathway was further increased by EtOH (less p50-activation), while p52 remained unaltered. Inhibition of non-canonical pathway was unchanged by EtOH. Conclusion: Here, alcohol's anti-inflammatory effects are mediated via decreasing nuclear levels of activated p50-subunit and canonical NF-kappa B signaling pathway. (C) 2017 The Author(s) Published by S. Karger AG, Basel
Keywords: Inflammation; Trauma; Alcohol; Intoxication; NF-kappa B; Canonical; Non-canonical; Lung

Ethanol, ethyl and sodium pyruvate decrease the inflammatory responses of human lung epithelial cells via Akt and NF-kappa B in vitro but have a low impact on hepatocellular cells - Relja, B.; Omid, N.; Wagner, N.; Moers, K.; Werner, I.; Juengel, E.; Marzi, I.; Perl, Mario (International Journal of Molecular Medicine, 2016)
Increases in pro-inflammatory cytokine levels and tissue-infiltrating leukocytes have been closely linked to increased systemic and local inflammation, which result in organ injury. Previously, we demonstrated the beneficial and hepatoprotective anti-inflammatory effects of acute ethanol (EtOH) ingestion in an in vivo model of acute inflammation. Due to its undesirable side-effects, however, EtOH does not represent a therapeutic option for treatment of acute inflammation. Therefore, in this study, we compared the effects of acute EtOH exposure with ethyl pyruvate (EtP) as an alternative anti-inflammatory drug in an in vitro model of hepatic and pulmonary inflammation. Human hepatocellular carcinoma cells Huh7 and alveolar epithelial cells A549 were stimulated with either interleukin (IL) IL-1 beta (1 ng/ml, 24 h) or tumor necrosis factor (TNF) (10 ng/ml, 4 h), and then treated with EtP (2.5-10 mM), sodium pyruvate (NaP, 10 mM) or EtOH (85-170 mM) for 1 h. IL-6 or IL-8 release from Huh7 or A549 cells, respectively, was measured by an enzyme-linked immunosorbent assay. Neutrophil adhesion to cell monolayers and CD54 expression were also analyzed. Bcl-2 and Bax gene expression was determined by RT-qPCR, and western blot analysis was performed to determine the mechanisms involved. Treating A549 cells with either EtOH or EtP significantly reduced the IL-1 beta- or TNF-induced IL-8 release, whereas treating Huh7 cells did not significantly alter IL-6 release. Similarly, neutrophil adhesion to stimulated A549 cells was significantly reduced by EtOH or EtP, whereas for Huh7 cells the tendency for reduced neutrophil adhesion rates by EtOH or EtP was not significant. CD54 expression was noticeably reduced in A549 cells, but this was not the case in Huh7 cells after treatment. The Bax/Bcl-2 ratio was dose-dependently decreased by EtOH and by high-dose EtP in A549 cells, indicating a reduction in apoptosis, whereas this effect was not observed in Huh7 cells. The underlying mechanisms involve reduced phosphorylation of Akt and nuclear factor-kappa B (NF-kappa B) p65. We noted that as with EtP, EtOH reduced the inflammatory response in lung epithelial cells under acute inflammatory conditions. However, due to the low impact which EtP and EtOH had on the hepatocellular cells, our data suggest that both substances exerted different effects depending on the cellular entity. The possible underlying mechanisms involved the downregulation of Akt and the transcription factor NF-kappa B, but further research on this subject is required.
Keywords: ethanol; ethyl pyruvate; liver; lung; inflammation; in vitro

Ethyl pyruvate ameliorates hepatic injury following blunt chest trauma and hemorrhagic shock by reducing local inflammation, NF-kappaB activation and HMGB1 release - Wagner, Nils; Dieteren, Scott; Franz, Niklas; Koehler, Kernt; Moers, Katharina; Nicin, Luka; Schmidt, Julia; Perl, Mario; Marzi, Ingo; Relja, Borna (PLoS ONE, 2018)
BackgroundThe treatment of patients with multiple trauma including blunt chest/thoracic trauma (TxT) and hemorrhagic shock (H) is still challenging. Numerous studies show detrimental consequences of TxT and HS resulting in strong inflammatory changes, organ injury and mortality. Additionally, the reperfusion (R) phase plays a key role in triggering inflammation and worsening outcome. Ethyl pyruvate (EP), a stable lipophilic ester, has anti-inflammatory properties. Here, the influence of EP on the inflammatory reaction and liver injury in a double hit model of TxT and H/R in rats was explored.MethodsFemale Lewis rats were subjected to TxT followed by hemorrhage/H (60 min, 35 +/- 3mm Hg) and resuscitation/R (TxT+H/R). Reperfusion was performed by either Ringer's lactated solution (RL) alone or RL supplemented with EP (50 mg/kg). Sham animals underwent all surgical procedures without TxT+H/R. After 2h, blood and liver tissue were collected for analyses, and survival was assessed after 24h.ResultsResuscitation with EP significantly improved haemoglobin levels and base excess recovery compared with controls after TxT+H/R, respectively (p<0.05). TxT+H/R-induced significant increase in alanine aminotransferase levels and liver injury were attenuated by EP compared with controls (p<0.05). Local inflammation as shown by increased gene expression of IL-6 and ICAM-1, enhanced ICAM-1 and HMGB1 protein expression and infiltration of the liver with neutrophils were also significantly attenuated by EP compared with controls after TxT+H/R (p<0.05). EP significantly reduced TxT+H/R-induced p65 activation in liver tissue. Survival rates improved by EP from 50% to 70% after TxT+H/R.ConclusionsThese data support the concept that the pronounced local pro-inflammatory response in the liver after blunt chest trauma and hemorrhagic shock is associated with NF-kappa B. In particular, the beneficial anti-inflammatory effects of ethyl pyruvate seem to be regulated by the HMGB1/NF-kappa B axis in the liver, thereby, restraining inflammatory responses and liver injury after double hit trauma in the rat.

Ethyl pyruvate reduces acute lung damage following trauma and hemorrhagic shock via inhibition of NF-kappa B and HMGB1 - Relja, Borna; Wagner, Nils; Franz, Niklas; Dieteren, Scott; Moers, Katharina; Schmidt, Julia; Marzi, Ingo; Perl, Mario (Immunobiology, 2018)
Objective: After blunt thoracic trauma (TxT) and hemorrhagic shock with resuscitation (H/R) intense local inflammatory response and cell loss frequently impair the pulmonary function. Ethyl pyruvate (EP) has been reported to improve the pathophysiologic derangements in models of acute inflammation. Here, we studied the effects of EP on inflammation and lung damage after TxT + H/R.Methods: Twenty four female Lewis rats (180-240 g) were randomly divided into 3 groups: two groups underwent TxT followed by hemorrhagic shock (35 +/- 3 mmHg) for 60 min and resuscitation with either Ringers-Lactat (RL) alone or RL supplemented with EP (EP, 50 mg/kg). Sham operated animals underwent surgical procedures. Two hours later bronchoalveolar lavage fluid (BAL), lung tissue and blood were collected for analyses.Results: EP significantly improved pO(2) levels compared to RL after TxT + H/R. TxT + H/R induced elevated levels of lactate dehydrogenase, total protein concentration in BAL and lung damage as evidenced by lung histology; these effects were significantly reduced by EP. Local inflammatory markers, lung TNF-alpha protein levels and infiltration with polymorphonuclear leukocytes (PMNL) significantly decreased in EP vs. RL group after TxT + H/R. Indicators of apoptosis as reduced BCL-2 and increased FAS gene expression after TxT + H/R were significantly increased or decreased, respectively, by EP after TxT + H/R. EP reduced TxT + H/R-induced p65 phosphorylation, which was concomitant with reduced HMGB1 levels in lung sections.Conclusions: Taken together, TxT + H/R induced strong inflammatory response and apoptotic changes as well as lung injury which were markedly diminished by EP. Our results suggest that this might be mediated via NF-kappa B and/or HMGB1 dependent mechanism.
Keywords: Pyruvate; Neutrophils; Lung; HMGB1; Apoptosis; Necrosis

ETHYL PYRUVATE REDUCES LUNG APOPTOSIS AND INFLAMMATION AFTER BLUNT CHEST TRAUMA AND HEMORRHAGIC SHOCK - Perl, Mario; Wagner, Nils; Franz, Niklas; Dieteren, Scott; Moers, Katharina; Marzi, Ingo; Relja, Borna (Shock, 2016)

Functional immune monitoring in severely injured patients—A pilot study - Halbgebauer, Rebecca; Kellermann, Stephanie; Schäfer, Fabian; Weckbach, Sebastian; Weiss, Manfred; Barth, Eberhard; Bracht, Hendrik; Kalbitz, Miriam; Gebhard, Florian; Huber-Lang, Markus S.; Perl, Mario (Scandinavian Journal of Immunology, 2019)
After severe trauma, the resulting excessive inflammatory response is countered by compensatory anti-inflammatory mechanisms. The systemic inflammatory response to trauma enhanced by inappropriately timed surgical second hits may be detrimental for the patient. On the other hand, overwhelming anti-inflammatory mechanisms may put patients at increased risk from secondary local and systemic infections. The ensuing sepsis and organ dysfunction due to immune dysregulation remain the leading causes of death after injury. To date, there are no clinically applicable techniques to monitor the pro-/anti-inflammatory immune status of the patients and the remaining ability to react to microbial stimuli. Therefore, in the present study, we used a highly standardized and easy-to-use system to draw peripheral whole blood from polytraumatized patients (ISS ≥ 32, n = 7) and to challenge it with bacterial lipopolysaccharide. Secreted cytokines were compared with those in samples from healthy volunteers. We observed a significant decrease in the release of monocyte-derived mediators. Surprisingly, we detected stable or even increased concentrations of cytokines related to T cell maturation and function. For clinical practicability, we reduced the incubation time before supernatants were collected. Even after an abbreviated stimulation period, a stable release of almost all analysed parameters in patient blood could be detected. In conclusion, the data are indicative of a clinically well-applicable approach to monitor the immune status in severely injured patients in a short time. This may be used to optimize the timing of necessary surgical interventions to avoid a boost of proinflammation and reduce risk of secondary infections.
CRIS-Team Scopus Importer:2019-11-19
Keywords: cytokines; human; inflammation; lipopolysaccharide

Immunomodulatory and cardio-protective effects of differentially originated multipotent mesenchymal stroma cells during polymicrobial sepsis in mice - Kanewska, Anna; Lackner, Ina; Friedrich, Anne; Winkelmann, Martina; Rojewski, Markus; Weber, Birte; Preßmar, Jochen; Perl, Mario; Schrezenmeier, Hubert; Kalbitz, Miriam (European Journal of Trauma and Emergency Surgery, 2025)
Purpose: Sepsis is a life-threatening condition with cardiac complications being an independent predictor of poor outcome. Although their mechanisms have been widely investigated, therapeutic options remain limited. One promising therapeutic tool are mesenchymal stromal cells (MSCs). The aim of this study is to investigate the immunomodulatory effects of human MSCs from two different sources (bone marrow/BMMSC and adipose tissue/ASC) and to evaluate their cardioprotective potential. Methods: 60 adult male C57BL/6 mice were divided into sham, sepsis (cecal ligation puncture (CLP)) and two i.v. treatment groups CLP + human BMMSC and CLP + human ASC with 5 animals in each group. The observation periods were 8, 24 and 72 h. Left ventricular tissue was analyzed histologically, by qPCR (C3ar, C5ar1, Il-1b, Il-6, Il-10, Tlr2, Tlr4, Tnfa, and Nlrp3) and western blot. Cardiac damage markers troponin I and heart fatty acid binding protein (HFABP) were detected in serum by ELISA. Results: Troponin I and HFABP were significantly increased in CLP group after 8 h compared to sham. In cardiac tissue the expression of C3ar, C5ar1, Il-1b, Il-6, Il-10, Tlr2, Tlr4, Tnfa and Nlrp3 inflammasome was upregulated up to 24h after CLP compared to sham. After BMMSC treatment, C3ar as well as C5ar, Tlr2 and Il-10 mRNA expression in left ventricle was downregulated compared to CLP, whereas ASC treatment was associated with the downregulation of Il-6 and Nlrp3. Conclusions: CLP-induced polymicrobial sepsis in mice was associated with cardiac damage and increased inflammation in left ventricular tissue. Therapeutic systemic application of human BMMSC and ASC ameliorated damage and inflammation in the heart.
CRIS-Team Scopus Importer:2025-05-02
Keywords: ASC treatment; BMMSC treatment; Cardiac dysfunction; CLP sepsis; Immunotherapy; Septic cardiomyopathy; Tissue regeneration

IMPORTANT ROLE OF HSP70 IN COMPLEMENT COMPONENT C5A-INDUCED DELAYED APOPTOSIS OF NEUTROPHIL GRANULOCYTES - Wiegner, R.; Denk, S.; Braumueller, S.; Huber-Lang, M.; Perl, Mario (Shock, 2014)

INFLUENCE OF ETHYL PYRUVATE ON ORGAN DAMAGE, INFLAMMATION AND OUTCOME AFTER BLUNT CHEST TRAUMA AND HEMORRHAGIC SHOCK IN VIVO - Wagner, Nils; Franz, Niklas; Dieteren, Scott; Moers, Katharina; Perl, Mario; Marzi, Ingo; Relja, Borna (Shock, 2016)

Intraoperative Navigation einer Distraktionsverletzung der BWS bei schwersten skoliotischen Veränderungen - Schramm, Simon; Groh, Johannes; Krause, Johannes; Perl, Mario (Die Unfallchirurgie, 2024)
The case of a 43-year-old male patient is described, who suffered several injuries due to a traffic accident, including a distraction injury to the thoracic spine. A specific feature of this case was the existing spondylodesis with material fracture and secondary loss of reduction. Due to this, the guidewires of the pedicle screws were placed in a navigation pattern in the absence of adjustable pedicles and an abnormal screw corridor. This guarantees an optimal positioning with associated patient safety.
CRIS-Team Scopus Importer:2024-05-10
Keywords: 3D imaging; Distraction injury; Multiple trauma; Navigation; Spinal trauma

Long-Term Outcomes Following Single-Stage Reamed Intramedullary Exchange Nailing in Apparently Aseptic Femoral Shaft Nonunion with Unsuspected Proof of Bacteria - Hackl, Simon; von Rüden, Christian; Trenkwalder, Katharina; Keppler, Lena; Hierholzer, Christian; Perl, Mario (Journal of Clinical Medicine, 2024)
Background: The aim of this study was to evaluate detection rates and risk factors for unsuspected proof of bacteria, as well as clinical and radiologic outcomes following femoral shaft nonunion without clinical signs of infection treated by a single-stage surgical revision procedure including reamed intramedullary exchange nailing. Methods: A retrospective cohort study was performed in a European level I trauma center between January 2015 and December 2022. Fifty-eight patients were included who underwent reamed intramedullary exchange nailing as a single-step procedure for surgical revision of posttraumatic diaphyseal femoral nonunion without any indications of infection in medical history and without clinical signs of local infection. Clinical details of the patients were analyzed and functional and radiologic long-term outcomes were determined. Results: In all patients, with and without proof of bacteria osseous, healing could be observed. The physical component summary of the SF-12 demonstrated significantly better results at least one year after the final surgical revision in case of a negative bacterial culture during exchange nailing. Conclusions: Clinical long-term outcomes demonstrated a trend towards better results following femoral shaft nonunion revision if there was no evidence for the presence of low-grade infected nonunion. In this case, a single-stage surgical procedure may be recommended.
CRIS-Team Scopus Importer:2024-03-22
Keywords: femur; fracture nonunion; intramedullary nail; low-grade infection; lower extremity functional scale (LEFS); outcome; septic; SF-12

Mapping tendon stiffness: Two-dimensional versus point shear wave elastography - Pasurka, Mario; Falck, Theo; Kubach, Joshua; Söllner, Stefan; Strobel, Deike; Perl, Mario; Betsch, Marcel (Journal of Orthopaedics, 2025)
Rationale and objectives: To date, no study has investigated the comparability between point shear wave elastography (pSWE) and 2D-shear wave elastography (2D-SWE) in assessing patellar tendon (PT) stiffness. In addition to comparing shear wave velocities, this study also evaluated intra- and interrater reliability, as well as measurement time. Materials and methods: Forty healthy subjects (20 females, 20 males; age: 23.3 ± 2.4 years, BMI: 22.46 ± 2.23 kg/m2) were recruited as participants. Each participant underwent a standardized multimodal ultrasound protocol that included B-mode ultrasound (B-US), Color Doppler ultrasound (CD-US), and a shear wave elastography (SWE) examination of the bilateral patellar tendon using both pSWE and 2D-SWE. Stiffness values and examination times were recorded. Intra- and interrater reliability were assessed across two different measurement time points with two investigators for both pSWE and 2D-SWE. Results: Elastography values were slightly higher for pSWE compared to 2D-SWE (pSWE: 4.02 ± 1.07 m/s, 2D-SWE: 3.82 ± 0.73 m/s; p < 0.001). 2D-SWE10 measurements took significantly more time than pSWE (2D-SWE10: 69.89 ± 13.46 s vs. pSWE: 54.85 ± 8.34 s, p < 0.001). However, the time required for 2D-SWE1 was significantly shorter than for pSWE (2D-SWE1: 47.20 ± 8.23 s vs. pSWE: 54.85 ± 8.34 s, p < 0.001). Both interrater and intrarater reliability reached excellent levels for all SWE measurements, with the highest interrater and intrarater ICC values obtained for 2D-SWE1. Conclusion: This is the first study to evaluate and compare pSWE and 2D-SWE in the assessment of patellar tendon stiffness. These findings could have important implications for the clinical use of musculoskeletal SWE, providing insights into measurement time, reliability, and the potential benefits of using 2D-SWE in clinical practice.
CRIS-Team Scopus Importer:2025-08-29
Keywords: Acoustic radiation force impulse imaging; Musculoskeletal ultrasound; Point shear-wave elastography; Tendon stiffness; Two-dimensional shear wave elastography

Minimal-invasive Stabilisierung bei thorakolumbalen osteoporotischen Frakturen - Schnake, Klaus John; Scheyerer, Max Josef; Spiegl, Ulrich Josef Albert; Perl, Mario; Ullrich, Bernhard Wilhelm; Grüninger, Sebastian; Osterhoff, Georg; Katscher, Sebastian; Sprengel, Kai (Unfallchirurg, 2020)
Background: Minimally invasive stabilization of thoracolumbar osteoporotic fractures (OF) in neurologically intact patients is well established. Various posterior and anterior surgical techniques are available. The OF classification and OF score are helpful for defining the indications and choice of operative technique. Objective: This article gives an overview of the minimally invasive stabilization techniques, typical complications and outcome. Material and methods: Selective literature search and description of surgical techniques and outcome. Results: Vertebral body augmentation alone can be indicated in painful but stable fractures of types OF 1 and OF 2 and to some extent for type OF 3. Kyphoplasty has proven to be an effective and safe procedure with a favorable clinical outcome. Unstable fractures and kyphotic deformities (types OF 3–5) should be percutaneously stabilized from posterior. The length of the pedicle screw construct depends on the extent of instability and deformity. Bone cement augmentation of the pedicle screws is indicated in severe osteoporosis but increases the complication rate. Restoration of stability of the anterior column can be achieved through additional vertebral body augmentation or rarely by anterior stabilization. Clinical and radiological short and mid-term results of the stabilization techniques are promising; however, the more invasive the surgery, the more complications occur. Conclusion: Minimally invasive stabilization techniques are safe and effective. The specific indications for the individual procedures are guided by the OF classification and the individual clinical situation of the patient.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Augmentation; Bone cements; Classification; Pedicle screws; Spine

Partial weight-bearing and range of motion limitation significantly reduce the loads at medial meniscus posterior root repair sutures in a cadaveric biomechanical model - Sukopp, Matthias; Schwab, Nina; Schwer, Jonas; Frey, Julian; Metzger, Jonas Walter; Ignatius, Anita; Perl, Mario; Salami, Firooz; Vogele, Daniel; Kappe, Thomas; Seitz, Andreas Martin (Knee Surgery Sports Traumatology Arthroscopy, 2024)
Purpose: The aim of this study was to investigate the influence of medial meniscus posterior root avulsion (MMPRA) before and after surgical treatment on the biomechanics of the knee joint, including suture repair forces during daily and crutch-assisted gait movements. Methods: MMPRA were investigated in eight human cadaver knee joint specimens by a dynamic knee joint simulator with daily (normal gait, gait with additional rotational movement, standing up, sitting down) and rehabilitation-associated movements (crutch-assisted gait with limited flexion range of motion [30°] and 30% [toe-touch weight-bearing, TTWB] and 50% of body weight [partial weight-bearing, PWB]) with simulated physiologic muscle forces. Each specimen was tested in intact, torn and repaired (transtibial suture) state. The biomechanical parameters were: medial mean contact pressure and area, knee joint kinematics, medial displacement of the posterior meniscus horn and loading on the anchoring suture. Results: Significant reduction of the contact area due to the avulsion was observed in all movements except for PWB and sitting down. MMPRA repair significantly increased the contact areas during all movements, bringing them to levels statistically indistinguishable from the initial state. MMPRA resulted in a medial displacement up to 12.8 mm (sitting down) and could be reattached with a residual displacement ranging from 0.7 mm (PWB) to 5.7 mm (standing up), all significantly (p < 0.001) reduced compared to the torn state. The mean peak anchoring suture load increased from TTWB (77 N), PWB (91 N) to normal gait (194 N), gait rotation (207 N), sitting (201 N; p < 0.01) and to standing up (232 N; p = 0.03). Conclusion: Surgical treatment of MMPRA allows restoration of physiological knee joint biomechanics. Crutch-assisted movements reduce the loading of the repair suture, thus likewise the risk for failure. From a biomechanical point of view, crutch-assisted movements are recommended for the early rehabilitation phase after MMPRA repair. Level of Evidence: Level V.
CRIS-Team Scopus Importer:2024-09-27
Keywords: dynamic knee joint simulator; knee contact mechanics; medial meniscus posterior root avulsion; rehabilitation protocol; suture repair

Patellaosteotomie kombiniert mit modifizierter Trochleaplastik und Tuberositasmedialisierung als Therapie der permanenten Patellaluxation in Beugung - Dickschas, Jörg; Schmeling, Arno; Perl, Mario; Simon, Michael (Zeitschrift für Orthopädie und Unfallchirurgie, 2023)
CRIS-Team Scopus Importer:2023-09-15

Polytrauma Management - Treatment of Severely Injured Patients in ER and OR - Von Rueden, Christian; Buehren, Volker; Perl, Mario (Zeitschrift für Orthopädie und Unfallchirurgie, 2017)
The adequate treatment of severely injured patients is challenging and can only be successfully executed when it starts at the accident site and is continued in all treatment phases including the early rehabilitation phase. Treatment should be performed by an interdisciplinary team guided by a trauma surgeon in order to adequately manage the severe injuries some of which are life-threatening. Treatment of polytrauma patients is a key task of certified trauma centers and must follow standardized guidelines. For a successful therapy of severely injured patients lifetime training at regular intervals in well-established polytrauma concepts is a mandatory requirement.
Keywords: Polytrauma; Damage Control Surgery; Damage Control Orthopedics; Early Total Care; ATLS; Schockraum; Traumazentrum; polytrauma; damage control surgery; damage control orthopedics; early total care; ATLS; emergency room

Precision and effort in robot-assisted placement of pedicle screws compared to standard surgical navigation - Sippel, Julia; Groh, Johannes; Bräuer, Lars; Perl, Mario; Stadthalter, Holger (Scientific Reports, 2024)
Aim was to compare image-guided navigation with a robot-assisted solution for performing MISS regarding precision, required time and subjective aspects. 90 pedicles were instrumented on two torsos, half with navigation, half robot-assisted. Precision analysis between both solutions didn’t show a significant difference. Time measurement showed a significantly longer duration per wire for the robot-arm on the first torso and a not significant longer duration on the second torso, where a significant reduction in the mean duration was shown. There was no significant difference in the subjective impressions comparing navigation and robot except the possibility to change the procedure. Precision of both methods is suitable for clinical use. A time advantage using the robot-arm couldn’t be demonstrated in the present study. A significant learning curve was shown, so a reduction in the longer duration on the robot can be expected. Further studies in clinical use are necessary.
CRIS-Team Scopus Importer:2024-11-22

Pre- or post-treatment with ethanol and ethyl pyruvate results in distinct anti-inflammatory responses of human lung epithelial cells triggered by interleukin-6 - Relja, Borna; Omid, Nina; Schaible, Alexander; Meier, Simon; Oppermann, Elsie; Lehnert, Mark; Marzi, Ingo; Perl, Mario (Molecular Medicine Reports, 2015)
Increased local and systemic levels of interleukin (IL)-6 are associated with inflammatory processes, including neutrophil infiltration of the alveolar space, resulting in lung injury. Our previous study demonstrated the beneficial anti-inflammatory effects of acute exposure to ethanol (EtOH) in an acute in vivo model of inflammation. However, due to its side-effects, EtOH is not used clinically. In the present study, the effects of EtOH and ethyl pyruvate (EtP) as an alternative anti-inflammatory drug prior to and following application of an IL-6 stimulus on cultured A549 lung epithelial cells were compared, and it was hypothesized that treatment with EtOH and EtP reduces the inflammatory potential of the A549 cells. Time- and dose-dependent release of IL-8 from the A549 cells was observed following stimulation with IL-6. The release of IL-8 from the A549 cells was assessed following treatment with EtP (2.5-10 mM), sodium pyruvate (NaP; 10 mM) or EtOH (85-170 mM) for 1, 24 or 72 h, prior to and following IL-6 stimulation. The adhesion capacities of neutrophils to the treated A549 cells, and the expression levels of cluster of differentiation (CD) 54 by the epithelial cells were measured. Treatment of the A549 cells with either EtOH or EtP significantly reduced the IL-6-induced release of IL-8. This effect was observed in the pre- and post-stimulatory conditions, which is of therapeutic importance. Similar data was revealed regarding the IL-6-induced neutrophil adhesion to the treated A549 cells, in which pre- and post-treatment with EtOH or EtP decreased the adhesion capacity, however, the results were dependent on the duration of incubation. Incubation durations of 1 and 24 h decreased the adhesion rates of neutrophils to the stimulated A549 cells, however, the reduction was only significant at 72 h post-treatment. The expression of CD54 was reduced only following treatment for 24 h with either EtOH or EtP, prior to IL-6 stimulation. Therefore, EtOH and EtP reduced the inflammatory response of lung epithelial cells, and the potential of EtP to mimic EtOH was observed in the pre- and post-treatment conditions.
Keywords: ethanol; ethyl pyruvate; lung; inflammation; in vitro

Radial head and neck fractures in children and adolescents - Kalbitz, Miriam; Lackner, Ina; Perl, Mario; Preßmar, Jochen (Frontiers in Pediatrics, 2023)
Background: Radial head and neck fractures are a rare entity in pediatric patients. Due to specific characteristics of the blood supply and remodeling potential, the correct diagnosis and initiation of appropriate therapy are crucial for the outcome. Therefore, the aim of this retrospective observational study was to present the outcome of a series of pediatric patients with radial head and neck fractures. Methods: In total, 67 pediatric and adolescent patients with a fracture of the proximal radius admitted to a Level I Trauma Center (Germany) between 2005 and 2017 were included in this retrospective observational study. Patients were stratified in accordance with the classification of Judet modified by Metaizeau and with the AO Pediatric Comprehensive Classification of Long Bone Fractures (AO-PCCF). Results: AO-PCCF fracture type of proximal radius was age-dependent. Epiphyseal axis angle and displacement angle correlated significantly. Fractures treated with a K-wire or embrochage centromedullaire elastique stable (ECMES) presented higher displacement angles. The duration of callus formation was dependent on both the reduction technique and fracture displacement. The range of motion after complete fracture consolidation was dependent on the Metaizeau type and reduction technique but independent of the duration of immobilization and physical therapy. Conclusion and clinical relevance: Both the epiphyseal axis and displacement angle are suitable for measuring the initial fracture displacement in radiographs. Consolidation is dependent on the initial displacement and reduction technique. The mini-open approach leads to a worse reduction result, later callus formation, and a more restricted range of motion in terms of pronation. Furthermore, the range of motion at follow-up is independent of the duration of immobilization and physiotherapy.
CRIS-Team Scopus Importer:2023-02-24
Keywords: AO-PCCF; children; Metaizeau; pediatric fracture; radial head fracture; radial neck fracture

Risk Factors for Failure in Conservatively Treated Osteoporotic Vertebral Fractures: A Systematic Review - Scheyerer, Max J.; Spiegl, Ulrich J.A.; Grueninger, Sebastian; Hartmann, Frank; Katscher, Sebastian; Osterhoff, Georg; Perl, Mario; Pumberger, Matthias; Schmeiser, Gregor; Ullrich, Bernhard W.; Schnake, Klaus J. (Global Spine Journal, 2021)
Study Design: Systematic review. Objectives: Osteoporosis is one of the most common diseases of the elderly, whereby vertebral body fractures are in many cases the first manifestation. Even today, the consequences for patients are underestimated. Therefore, early identification of therapy failures is essential. In this context, the aim of the present systematic review was to evaluate the current literature with respect to clinical and radiographic findings that might predict treatment failure. Methods: We conducted a comprehensive, systematic review of the literature according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) checklist and algorithm. Results: After the literature search, 724 potentially eligible investigations were identified. In total, 24 studies with 3044 participants and a mean follow-up of 11 months (range 6-27.5 months) were included. Patient-specific risk factors were age >73 years, bone mineral density with a t-score <−2.95, BMI >23 and a modified frailty index >2.5. The following radiological and fracture-specific risk factors could be identified: involvement of the posterior wall, initial height loss, midportion type fracture, development of an intravertebral cleft, fracture at the thoracolumbar junction, fracture involvement of both endplates, different morphological types of fractures, and specific MRI findings. Further, a correlation between sagittal spinal imbalance and treatment failure could be demonstrated. Conclusion: In conclusion, this systematic review identified various factors that predict treatment failure in conservatively treated osteoporotic fractures. In these cases, additional treatment options and surgical treatment strategies should be considered in addition to follow-up examinations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: compression fracture; osteoporotic fracture; risk factor; treatment failure

Role of Complement C5 in Experimental Blunt Chest Trauma-Induced Septic Acute Lung Injury (ALI) - Kalbitz, Miriam; Karbach, Michael; Braumueller, Sonja; Kellermann, Philipp; Gebhard, Florian; Huber-Lang, Markus; Perl, Mario (PLoS ONE, 2016)
BackgroundSevere blunt chest trauma is associated with high mortality. Sepsis represents a serious risk factor for mortality in acute respiratory distress syndrome (ARDS). In septic patients with ARDS complement activation products were found to be elevated in the plasma. In single models like LPS or trauma complement has been studied to some degree, however in clinically highly relevant double hit models such as the one used here little data is available. Here, we hypothesized that absence of C5 is correlated with a decreased inflammatory response in trauma induced septic acute lung injury.Methods12 hrs after DH in mice the local and systemic cytokines and chemokines were quantified by multiplex bead array or ELISA, activated caspase-3 by western blot. Data were analyzed using one-way ANOVA followed by post-hoc Sidak's multiple comparison test (significance, p <= 0.05).ResultsIn lung tissue interleukin (IL)-6, monocyte chemo attractant protein-1 (MCP-1) and granulocyte-colony stimulating factor (G-CSF) was elevated in both C5(-/-) mice and wildtype littermates (wt), whereas caspase-3 was reduced in lungs after DH in C5(-/-) mice. Systemically, reduced keratinocyte-derived chemokine (KC) levels were observed after DH in C5(-/-) compared to wt mice. Locally, lung myeloperoxidase (MPO), protein, IL-6, MCP-1 and G-CSF in brochoalveolar lavage fluid (BALF) were elevated after DH in C5(-/-) compared to wt.ConclusionsIn the complex but clinically relevant DH model the local and systemic inflammatory immune response features both, C5-dependent and C5-independent characteristics. Activation of caspase-3 in lung tissue after DH was C5-dependent whereas local inflammation in lung tissue was C5-independent.

Self-inflicted partial epiphyseolysis of the distal femur-a case report. - Kanewska, Anna; Krause, Johannes; Perl, Mario (Frontiers in Pediatrics, 2025)
INTRODUCTION: Injuries to the epiphyseal plate are of great concern as they can affect bone growth. Although epiphyseal fractures are common in adolescents, fractures of the distal femoral epiphyseal plate are rare. CASE PRESENTATION: We present a case of a Salter-Harris type 1 fracture of the distal epiphysis of the femur that was self-inflicted by a patient with paraplegia due to spina bifida. The patient was brought to the pediatrician's attention during a routine checkup with an apparent swelling of the right thigh. Upon presentation, we performed a radiograph and an additional MRI, which revealed a partial ventero-medial epiphyseolysis, consistent with a Salter-Harris type 1 fracture. Due to the dislocation, we indicated closed reduction with K-wires. Repositioning was performed using a modified Kapandji maneuver and was completed with additional K-wires. CONCLUSION: Distal epiphyseolysis is a relatively rare injury that can lead to serious complications. Therefore, although rare, epiphyseal fractures should be considered in pediatric patients presenting with uncertain limb swelling.
EVALuna2:594597

Sera from severe trauma patients with pneumonia and without infectious complications have differential effects on neutrophil biology - Relja, Borna; Taraki, R.; Teuben, M. P. J.; Moers, K.; Wagner, N.; Wutzler, S.; Hildebrand, Frank; Marzi, I.; Perl, Mario (BMC Pulmonary Medicine, 2016)
Background: Major trauma patients (TP) developing imbalanced immune response are at high risk for infectious post-injury complications including pneumonia. Neutrophils play a central role in the host defense against bacteria and thereby pathogenesis of infections. While there are numerous studies about neutrophil function after trauma, data about their biology in patients who suffer from pneumonia following trauma are sparse. Here, we studied the effect of serum isolated from patients who do and do not develop infection (inf.) on the biology of neutrophils from healthy volunteers.Methods: Sera samples from eighteen TP with an injury severity score above 16 were obtained. Nine patients were grouped to no inf. group (TP without pneumonia), and nine to inf. group (TP with pneumonia). Samples were obtained at admission to emergency department (ED), a day prior pneumonia diagnosis (1 d prior inf) or at the day of diagnosis (1 d prior inf). Samples from the equal post-injury days in the corresponding no inf. group were used. Neutrophils from nine healthy volunteers were isolated. Effects for sera isolated from infected and non-infected patients on neutrophil biology were analyzed. Migratory capacity of neutrophils towards TP's serum, their CD11b and CD62L membrane receptor expression and oxidative burst activity after stimulation with TP's serum were determined and compared between groups.Results: Migratory capacity of neutrophils was significantly increased after trauma and persisted during the study period. CD11b expression in all groups was significantly increased. CD62L expression decreased generally in samples from ED and recovered later to baseline. Stratifying no inf. and inf. groups showed significantly decreased migratory capacity, increased CD11b and significantly decreased CD62L expression in the no inf. group. These differences persisted during the complete observational period. ROS production was strongly reduced in the no inf. group compared to the inf. group at later experimental time points.Conclusions: This data indicate that patients at risk for pneumonia development have differentially and early activated neutrophils following trauma compared to patients who are not at risk for post-injury complication. Studies about the differential biology of neutrophils and their immediately after trauma modified activity depending on the post-injury clinical course are warranted, and may deliver predictive or even therapeutic strategies to control inflammation.
Keywords: Trauma; Pneumonia; Neutrophils; CD31; CD62L; Migration; Oxidative burst

Severe blunt thoracic trauma caused by ski collision - Lochner, S. J.; Scherr, M.; Perl, Mario; Grove, C. (Unfallchirurg, 2017)
An approximately 25-year-old skier collided in a ski-run intersection. At high speed, he first hit another skier and then smashed into a snow cannon. He died from his injuries a short time later in hospital. A whole-body CT scan was conducted under resuscitation conditions, which was followed by an autopsy. The investigation revealed a severe blunt thoracic trauma as cause of death. The detailed analysis was the result of the combination of the two methods of investigation, CT scan and autopsy. The methods complemented each other effectively and allowed for a detailed presentation of the injury pattern. In conjunction with the additional analytical accident report, this combination of CT scan and autopsy contributes towards a reconstruction of accidents and the development of prevention measures and related protective systems.
Keywords: Skiing accident; Blunt thoracic trauma; Whole-body CT scan (with LUCAS); Autopsy; Protection systems

Suppression of the interleukin-1 beta-induced inflammatory response of human Chang liver cells by acute and subacute exposure to alcohol: an in vitro study - Moers, Katharina; Kany, Shinwan; Hoerauf, Jason-Alexander; Wagner, Nils; Neunaber, Claudia; Marzi, Ingo; Relja, Borna; Perl, Mario (Croatian Medical Journal, 2018)
Aim To evaluate protective immunosuppressive dose and time-dependent effects of ethanol in an in vitro model of acute inflammation in human Chang liver cells.Method The study was performed in 2016 and 2017 in the research laboratory of the Department of Trauma, Hand and Reconstructive Surgery, the University Hospital of the Goethe-University Frankfurt. Chang liver cells were stimulated with either interleukin (IL)-1 beta or IL-6 and subsequently treated with low-dose ethanol (85 mmol/L) or high-dose ethanol (170 mmol/L) for one hour (acute exposure) or 72 hours (subacute exposure). IL-6 and IL-1 beta release were determined by enzyme-linked immunosorbent assay. Neutrophil adhesion to Chang liver monolayers, production of reactive oxygen species, and apoptosis or necrosis were analyzed.Results Contrary to high-dose ethanol, acute low-dose ethanol exposure significantly reduced IL-1 beta-induced IL-6 and IL-6-induced IL-1 beta release (P < 0.05). Subacute ethanol exposure did not change proinflammatory cytokine release. Acute low-dose ethanol exposure significantly decreased inflammation-induced formation of reactive oxygen species (P < 0.05) and significantly improved cell survival (P < 0.05). Neither acute nor subacute high-dose ethanol exposure significantly changed inflammation-induced changes in reactive oxygen species or survival. Acute and subacute ethanol exposure, independently of the dose, significantly decreased neutrophil adhesion to inflamed Chang liver cells (P < 0.05).Conclusion Acute treatment of inflamed Chang liver cells with ethanol showed its immunosuppressive potential. However, the observed effects were limited to low-dose setting, indicating the relevance of ethanol dose in the modulation of inflammatory cell response.

The distribution of lateral rib fractures: a validation and further development of the AO/OTA classification system in patients with fractures at the rib shaft - Groh, Johannes; Kern, Florian; Krause, Johannes; Perl, Mario; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2025)
Introduction: Rib fractures are prevalent and clinically significant injuries, often associated with thoracic trauma. Despite their frequency, the precise distribution and characteristics of rib shaft fractures remain underexplored. This study investigates the distribution, location, and classification of lateral rib fractures using the AO/OTA classification, focusing on fracture patterns and the relationship to neighbored ribs. Methods: The study retrospectively analyzed 116 patients with 617 isolated rib fractures treated at a Level 1 trauma center over seven years. Using CT scans, fractures between the tubercle and osteochondral junction of the rib shaft were examined. Fracture type, dislocation, and location were categorized according to AO standards. The 116 patients underwent detailed statistical analysis to identify distribution patterns and correlations between fracture characteristics. Results: The fractures predominantly occurred between the fifth and seventh ribs, with a focus in the anterolateral to lateral region (40°–69°). Type A fractures were more anteriorly located, while type B fractures and dislocations shifted posteriorly. A regression analysis confirmed the significance of fracture type and dislocation in determining fracture position. Moreover, fractures showed clustering patterns, with adjacent ribs more likely to be injured. A caudal shift in fracture density and localization from the cranial to the caudal thorax was also observed. Discussion and conclusion: The findings validate the AO/OTA classification for rib fractures, highlighting the need for refined subsegmental divisions within the rib shaft for more precise clinical application. The study underscores the relationship between fracture location, type, and associated injuries, advocating for multicenter studies and a comprehensive classification system for thoracic trauma. This could enhance our understanding of injury patterns and inform treatment strategies.
CRIS-Team Scopus Importer:2025-03-07
Keywords: AO/OTA classification system; Chest wall injury; Flail chest; Rib fracture; Rib shaft

The immune response after fracture trauma is different in old compared to young patients - Vester, Helen; Huber-Lang, Markus S.; Kida, Qerim; Scola, Alexander; Van Griensven, Martijn; Gebhard, Florian; Nussler, Andreas K.; Perl, Mario (Immunity & Ageing, 2014)
Background: Despite significant medical progress and improved treatment, surgical procedures of proximal femur fractures in older patients are still associated with a high postoperative complication and mortality rate. Recently, several authors investigated the phenomenon of immunoageing, indicating differences in the ageing immune system.The aim of the present multi-center prospective clinical trial was to analyze differences in the posttraumatic immune response of old patients compared to young patients.Methods: Blood was collected from young patients (< 50 y, n = 20) with long bone fractures (YF), old patients (> 70 y, n = 21) with proximal femur fractures ( OF) upon clinical admission and within 6 hours after surgery, and two healthy age matched control groups (YH & OH). Serum TRAIL- and cytokine concentrations were analyzed via cytometric bead array, Fas-Ligand and TNF-Receptor-I via ELISA. CD15(+) magnetic bead-isolated neutrophils (PMN) were TUNEL stained.Results: IL-6 was significantly increased only in OF after trauma and surgery whereas YF patient exhibited a marked decrease of TNF after trauma. Interestingly, a significant increase of GM-CSF serum levels was observed in YF only, whereas OF exhibited a decrease of systemic IFN-gamma concentrations after trauma and after surgery. The healthy controls, old and young, had more or less similar inflammation levels. Moreover, TRAIL serum levels were diminished in OF after trauma and even further after surgery whereas in YF this was only observed after the surgical procedure. Fas-L concentrations were reduced only in YF after surgery or trauma. PMN apoptosis was significantly reduced only in YF, indicating activation of the innate immune system.Discussion: In summary, our data suggest that the posttraumatic immune response is differently regulated in old and young trauma patients. The operative procedure further impacts these differences after trauma. Whether the decreased activation of PMNs and phagocytes along with the observed dysregulation of the posttraumatic inflammatory response contributes to the high perioperative mortality rate of the elderly suffering from a proximal femoral fracture requires further investigation.
Keywords: Immunoageing; Trauma; Apoptosis; Inflammation

THE IMMUNE RESPONSE AFTER TRAUMA - IS IT DIFFERENT IN THE ELDERLY? - Vester, H.; Huber-Lang, M. S.; Kida, Q.; Gebhard, F.; Nussler, A. K.; Seeliger, C.; Van Griensven, Martijn; Perl, Mario (Shock, 2014)

The molecular fingerprint of lung inflammation after blunt chest trauma - Ehrnthaller, Christian; Flierl, Michael; Perl, Mario; Denk, Stephanie; Unnewehr, Heike; Ward, Peter A.; Radermacher, Peter; Ignatius, Anita; Gebhard, Florian; Chinnaiyan, Arul; Huber-Lang, Markus (European Journal of Medical Research, 2015)
Background: After severe blunt chest trauma, the development of an acute lung injury (ALI) is often associated with severe or even lethal complications. Especially in multiple injured patients after blunt chest trauma ALI/ARDS [acute respiratory distress syndrome (ARDS)] is frequent. However, in the initial posttraumatic phase, inflammatory clinical signs are often not apparent and underlying changes in gene-expression profile are unknown.Methods: Therefore, inflammation in lung tissue following blunt chest trauma was characterized in a well-defined bilateral lung injury model. Using DNA microarrays representing 9240 genes, the temporal sequence of blunt chest trauma-induced gene-expression patterns in lung tissue was examined.Results: The results suggest an activation of a highly complex transcriptional program in response to chest trauma. Chest trauma led to elevated expression levels of inflammatory and coagulatory proteins (such as TNF alpha receptor, IL-1 alpha, IL-1 beta, C3, NF-kappa B and plasminogen activator). However, upregulation of proteins was found, usually incoherent of exerting effects in blunt thoracic trauma (pendrin, resistin, metallothionein and glucocorticoid-induced leucine zipper). Furthermore, significant downregulation was observed as early as 10 min after trauma for cytokines and complement factors (LCR-1, C4) as well as for intracellular signaling molecules (inhibitory protein phosphatase) and ion-channels (voltage-dependent Ca2+ channel).Conclusions: Taken together, the provided global perspective of the inflammatory response following blunt chest trauma could provide a molecular framework for future research in trauma pathophysiology.
Keywords: Blunt chest trauma; Inflammation; Microarray; Transcription program

The newmedical treatment procedure of the German Statutory Accident Insurance: From the perspective of BG hospitals - Buehren, V.; Perl, Mario (Unfallchirurg, 2016)
The Hospital Group of the Statutory Accident Insurance (BG hospitals) was affected by the new requirements for severe injury procedures (SAV) in the same manner as all other maximum care hospitals. Simultaneously, the BG clinics were merged to form a centrally organized hospital group. A substantial need for adjustment existed for specialties, such as neurosurgery and visceral surgery at some sites. Needless to say, all trauma victims benefit from the high standards required by the Statutory Accident Insurance regardless of their insurance status. The provision of medical treatment with respect to its implementation into routine practice must be further optimized and additions, e.g. for the occurrence of complications are necessary.
Keywords: Concentration process; Centralization; German Statutory Accident Insurance; Severe injury procedures (SAV); Injury procedures (VAV)

The pararectus approach for internal fixation of acetabular fractures involving the anterior column: evaluating the functional outcome. - Von Rueden, Christian; Wenzel, Lisa; Becker, Johannes; Thannheimer, Andreas; Augat, Peter; Woltmann, Alexander; Buehren, Volker; Perl, Mario (International Orthopaedics, 2019)
INTRODUCTION: Aim of this retrospective analysis of prospectively collected data was to evaluate the functional mid-term outcome two years after open reduction and internal fixation of acetabular fractures involving the anterior column with affection of the quadrilateral plate using the pararectus approach on a large cohort. METHOD: Fifty-two patients (12 female, 40 male) with a median age of 55 (range 18-90) years and displaced acetabular fractures involving the anterior column were surgically treated in a single level I trauma centre between July 2012 and February 2016 using the pararectus approach. Thirty-four patients (8 female and 26 male) with a median age of 58 (range 20-85) years were available for complete clinical follow-up at regular intervals, finally 24 months post-operatively. Functional outcome was evaluated according to modified Merle d'Aubigné score, Lower Extremity Functional Scale, WOMAC, and SF-36. RESULTS: Range of time between trauma and surgical treatment was three (range 0-19) days. Operation time was 140 (range 60-240) minutes, and duration of hospital treatment was 19 (range 7-38) days. Functional results in 34 patients available for final follow-up demonstrated 68 points (median; range 39-80) according to the Lower Extremity Functional Scale, 6% according to the WOMAC (mean; SD ± 14.5%), and 69% (mean; SD ± 20.1%) according to the SF-36. The modified Merle d'Aubigné score was excellent in 22 patients, good in eight patients, and fair in four patients. DISCUSSION/CONCLUSION: Based on the good to excellent functional mid-term follow-up results of this study, the pararectus approach can be recommended as sufficient alternative single access to address displaced acetabular fractures involving the anterior column, independent of patients' age.
EVALuna2:415871

The Pararectus Approach in Acetabular Surgery: Radiological and Clinical Outcome - Wenzel, Lisa; von Rüden, Christian; Thannheimer, Andreas; Becker, Johannes; Brand, Andreas; Augat, Peter; Perl, Mario (Journal of Orthopaedic Trauma, 2020)
OBJECTIVES: To evaluate radiological fracture reduction and clinical results using the pararectus approach in complex acetabular fractures involving the anterior column. DESIGN: Retrospective database analysis of prospectively collected data. SETTING: Level 1 trauma center. PATIENTS/PARTICIPANTS: 61 patients (48 male and 13 female) with a median age of 55 (range 17-91) years were included. According to the chosen surgical approach, they were divided into 2 groups. The P-group included 43 patients, among them 32 male and 11 female patients with a median age of 55 (range 17-90) years. Eighteen patients [16 male, 2 female; median age: 53 (range 23-91) years] were treated through the ilioinguinal approach (I-group). INTERVENTION: Anterior surgical procedures through the pararectus or the ilioinguinal approach. MAIN OUTCOME MEASURED: Reduction results were rated according to the modified Matta criteria using a measurement protocol of hip joint gaps and steps in computed tomography scans. Operation time, complications, and clinical outcomes median one year postoperatively were compared. RESULTS: In the pararectus group reduction was anatomical in 21 out of 40 analyzed patients (52.5%), imperfect in 11 patients (27.5%), and poor in 8 patients (20%). The mean joint step reduction was 3.7 mm, and the mean joint gap reduction was 12.1 mm. In the ilioinguinal group reduction was anatomical in 9 out of 18 patients (50%), imperfect in 4 patients (22%), and poor in 5 patients (28%). The mean joint step reduction was 1 mm, and the mean joint gap reduction was 7 mm. Operation time was significantly shorter in the P-group (mean: 49 minutes; P < 0.001). CONCLUSIONS: This study indicates that acetabular fracture reduction using the pararectus approach is at least comparable with the ilioinguinal approach independent of patients' age. A relevant advantage of the pararectus approach was seen in a significantly shorter operation time. LEVEL OF EVIDENCE: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.
CRIS-Team Scopus Importer:2020-02-04

The Position of Functional Senior Doctor at German University Clinics - Muenzberg, M.; Perl, Mario (Unfallchirurg, 2014)

The role of low-grade infection in the pathogenesis of apparently aseptic tibial shaft nonunion - Hackl, Simon; Keppler, Lena; Von Rueden, Christian; Friederichs, Jan; Perl, Mario; Hierholzer, Christian (Injury-International Journal of the Care of the Injured, 2021)
Purpose: Aim of this study was to determine the rate of low-grade infection in patients with primarily as aseptic categorized tibial shaft nonunion and lack of clinical signs of infection.
CRIS-Team WoS Importer:2021-11-26

The Summer School of the German Society for Orthopaedics and Traumatology - A Success Story - Merschin, D.; Mutschler, M.; Stange, R.; Kopschina, C.; Schuettrumpf, P.; Doepfer, A. K.; Achatz, G.; Niethard, M.; Hoffmann, R.; Kladny, B.; Muenzberg, M.; Perl, Mario (Zeitschrift für Orthopädie und Unfallchirurgie, 2016)
Background: It has been known for several years that orthopaedic and trauma clinics suffer from a shortage of young people, due to the substantial loss in attractiveness. The Youth Forum OU has been addressing this problem for many years, by initiating many projects such as the Summer School to counteract this trend. The purpose of this research is to evaluate the success of Summer Schools since 2009.Methods: The Youth Forum OU performed a survey in December 2014 to answer the research question on the basis of an internet-based poll of the student participants in all Summer Schools between 2009 and 2014. Following data cleansing, 121 students and former students were included in the survey.Results: Seventy-two completed questionnaires were collected and included in the evaluation. The survey included 40% of Summer School participants, with a mean age of 27.3 years (SD +/- 2.95); 50% were female. Participation in the Summer School helped 50% of the respondents to decide to start advanced study in orthopaedics and/or traumatology (OU). One third of these Summer School participants had already finished a university degree; 100% are now residents in orthopaedics and/or traumatology. Regardless of prior plans, 87.2% of participants are now residents in OU. Thirty-three are still students: 78.8% have already decided to work in OU. The survey also served to identify the factors positively and negatively associated with OU. Unfavourable factors included the reputation of OU, and the difficulty of reconciling family and work. Favourable factors included surgical work and personal experience during university studies.Discussion: The aim of this study was to evaluate whether the efforts of the Youth Forum OU, the German Society for Orthopaedics and Traumatology (DGOU) and the local hospitals lead to increased interest in OU. The answer to this question is positive. This is particularly true for those students who did not plan to become an orthopaedic or trauma surgeon before participating in a Summer School. In conclusion, the efforts to recruit residents for OU by using Summer Schools were successful. Moreover, this research offers approaches to counteract the loss of attractiveness of OU.
Keywords: promotion of the young; residency; shortage of residents; youth forum

The weekend effect in pelvic fractures and influence of weekday and weekend accident days: a retrospective study of the German Pelvic Registry - Audretsch, Christof K.; Menger, Maximilian M.; Höch, Andreas; Histing, Tina; Rollman, Mika F.; Braun, Benedikt J.; Küper, Markus A.; Herath, Steven C.; Marintschev, Ivan; Mäder, Marcel; Osche, David; Osterhoff, Georg; et al. (Scientific Reports, 2025)
Treatment of pelvic fractures requires extensive human and material resources. The weekend is characterized by a reduced availability of these resources. In addition, weekend leisure activities lead to different injury patterns. The ‘weekend effect’, which describes these conditions, is controversially discussed in medicine. However, there is still a paucity of data, especially in traumatology and particularly in relation to pelvic injuries. The aim of this work is to assess the weekend effect on demographics, injury patterns and outcome in relation to the day of the accident. Demographic, clinical and operative parameters from the data of the German Pelvic Trauma Registry were retrospectively evaluated (n = 16,359). Differences between weekend and weekday accidents were statistically evaluated. Weekend accidents affect younger, more severely injured and less often female patients with fewer displaced fractures and a lower proportion of acetabular fractures. This results in less frequent operative treatment, but more emergency and early definitive surgery. In contrast to the numerous and significant differences in baseline conditions, the outcome in terms of quality of surgical treatment, morbidity and mortality showed only marginal and non-significant differences between weekend and weekday accidents. Weekend accidents differ from weekday accidents in their initial conditions. This does not lead to more frequent—yet more emergency and more early definitive surgeries. However, there are no differences in the quality of care or outcome according to the day of the accident.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Acetabular fracture; Complication; Injury pattern; Mortality; Pelvic ring fracture; Pelvic trauma; Treatment quality; Weekend effect

Transtuberositäre, ventral öffnende hohe Tibiaosteotomie zur Korrektur eines negativen Slope - Harrer, Jörg; Ferner, Felix; Lutter, Christoph; Petersen, Wolf; Perl, Mario; Simon, Michael (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
CRIS-Team Scopus Importer:2025-02-28

Traumatic fractures of the sternum – typical distribution and need for subgroups within AO and OTA classification system? - Groh, Johannes; Kern, Florian; Schenderlein, Anne; Krause, Johannes; Perl, Mario; Schulz-Drost, Stefan (European Journal of Trauma and Emergency Surgery, 2025)
Introduction: Objective of this study is the morphologic validation of the AO-classification of the sternal bone and particularly define subgroups. Methods: Analyzed were all patients of a level I trauma center of a 7-year period with fractures of the sternal bone and the anterior rib cartilage. A total number of n = 124 patients was included. The detailed evaluation of the CT-data recorded anatomical basic data of the rib cage and every fracture with its position, dislocation, fracture pattern (which was classified following the AO). Results: 116 (93.5%) patients showed 134 single fractures of the sternal bone, 48 (35.8%) of the manubrium, 81 (60.4%) of the corpus sterni and 5 (3.7%) of the xyphoid. 16 patients had a dual fracture of manubrium and corpus. Fractures of the corpus were mostly type A-fractures, followed by type B-and C-fractures. Manubrial fractures had the same number of type A- and B-fractures. Subgroups were theoretically defined by the senior author of our group and validated. based on location, dislocation and course of the fracture. Discussion: Sternal fractures are mostly shown at the corpus. Fractures of the xiphoid are very uncommon. Generally, corpus fractures are simple fractures, the rarer manubrium fractures show more complex fractures, which presumes a high trauma energy. The defined subgroups can help draw conclusion to the trauma mechanism and its potential concomitant injuries.
CRIS-Team Scopus Importer:2025-07-10
Keywords: AO/OTA classification system; Chest wall injury; Manubrium; Sternal fracture; Sternum fracture

Young doctors wanted - but how many? Current data on the number of aspiring specialist doctors in orthopedics and trauma surgery in Germany - Muenzberg, Matthias; Sotow, Barbara; Hoffmann, Reinhard; Kladny, Bernd; Stange, Richard; Mutschler, Manuel; Perl, Mario (Unfallchirurg, 2017)
There is an ongoing discussion about demographic change, a possible lack of young doctors and its impact on the healthcare system in Germany. Up to now, no valid data has been available on the exact numbers of residents in orthopedics and trauma surgery. Therefore, the aim of this study was to determine the actual number of residents in Germany in 2013/2014. We generated a database with all eligible providers of postgraduate training in orthopedics and trauma surgery in Germany. All of these were asked to fill out a questionnaire about the number of trainees, their gender and year of training. We achieved an 80% response rate (1509 questionnaires). Within these institutions, 4310 residents are trained. For Germany, this means an estimated number of about 5300 residents in the year 2013/2014. Ninety percent of postgraduate training is performed within a hospital and one-third of the residents are female. Looking at the expected number of doctors who will retire within the next five years, there seems to be enough young doctors to fill the gap. However, by 2040, an increased demand for othopedic and trauma surgeons is experted. Thus, we recommend centrally analyzing and coordinating the demand of residents in orthopedics and trauma surgery in Germany.
Keywords: Demand analysis; Residents; Post-graduate education; Orthopedics; Trauma surgery